Factors underlying the economic migration of German women to Poland - Marks-Bielska, Renata (Olsztyn Economic Journal, 2019)
The aim of the research and analysis was to identify the factors which contribute to stimulating entrepreneurial spirit among women. Special attention was paid to German women who had undertaken business activity in Poland. Based on a survey, it was determined that apart from such barriers to developing business as experienced by all businessmen (e.g. ensuring cash flows, having a sound knowledge of laws and regulations connected with business, and being competitive in the market), a female entrepreneur must meet other challenges arising from the position of a woman in society. Women’s determination in the pursuit of business did not depend on gender or émigré status, but on their willingness to start a business in a culturally foreign environment. The respondents emphasized that they were highly active and goal-oriented. Women would rather be perceived as entrepreneurs than as women or migrants, because the characteristics assigned to the two latter roles do not coincide with the typical image of ‘male entrepreneurship’.